A post-hoc subgroup analysis of data from a six month clinical trial comparing the efficacy and safety of losmapimod in moderate-severe COPD patients with ≤2% and >2% blood eosinophils. Issue 7 (July 2015) - Marks-Konczalik, Joanna; Costa, Maria; Robertson, Jon; McKie, Elizabeth; Yang, Shuying; Pascoe, Steven
Summary Background A six month study of the p38 MAPK inhibitor, losmapimod, suggested a trend in reducing COPD exacerbations with the 15 mg twice daily dose. Objective and methods Using data from this study which evaluated the efficacy of twice daily losmapimod, 2.5 mg, 7.5 mg, and 15 mg, versus placebo in patients with moderate-to-severe COPD, we analysed the effect of losmapimod in reducing the rate of moderate/severe exacerbations in patient subgroups with ≤2% and >2% blood eosinophils at baseline. Lung function, fibrinogen and hsCRP were also evaluated. Results In the ≤2% eosinophil subgroup, there was an exposure-related reduction in the rate of moderate/severe exacerbations with losmapimod relative to placebo (losmapimod 15 mg: 55% reduction; losmapimod 7.5 mg: 29%; losmapimod 2.5 mg: 10%); with the 15 mg dose reaching statistical significance (15 mg/placebo mean rate ratio [95% CI]: 0.45 [0.22; 0.90]). There was also an improvement in lung function with 15 mg losmapimod over Weeks 1–12. No improvement in the rate of moderate/severe exacerbations or post-bronchodilator FEV1 was observed for subjects treated with Losmapimod compared to placebo in the patient subgroup with blood eosinophils >2% at baseline. Transient reductions in fibrinogen and hsCRP were observed with losmapimod 7.5 mg and 15 mg in both eosinophil subgroups. Conclusions These findings indicate eosinophil-related heterogeneity within COPD and suggest that losmapimod could be a potential therapy to reduce exacerbations in COPD patients with eosinophil levels ≤2%. This needs to be explored further in a prospectively designed study with pre-specified criteria for blood eosinophil subgroups in COPD patients.